Presentation_1_Complete Lipopolysaccharide of Piscirickettsia salmonis Is Required for Full Virulence in the Intraperitoneally Challenged Atlantic Salmon, Salmo salar, Model.pptx - Valeska Herrera; Nicole Olavarría; José Saavedra; Yassef Yuivar; Patricio Bustos; Oscar Almarza; Marcos Mancilla (2022)
Bacterial cell envelopes play a critical role in host-pathogen interactions. Macromolecular components of these structures have been closely linked to the virulence of pathogens. Piscirickettsia salmonis is a relevant salmonid pathogen with a worldwide distribution. This bacterium is the etiological agent of piscirickettsiosis, a septicemic disease that causes a high economic burden, especially for the Chilean salmon farming industry. Although P. salmonis has been discovered long ago, its pathogenicity and virulence mechanisms are not completely understood. In this work, we present a genetic approach for producing in-frame deletion mutants on genes related to the biosynthesis of membrane-associated polysaccharides. We provide a detailed in vitro phenotype description of knock-out mutants on wzx and wcaJ genes, which encode predicted lipopolysaccharide (LPS) flippase and undecaprenyl-phosphate glucose phosphotransferase enzymes, respectively. We exhibit evidence that the wzx mutant strain carries a defect in the probably most external LPS moiety, while the wcaJ mutant proved to be highly susceptible to the bactericidal action of serum but retained the ability of biofilm production. Beyond that, we demonstrate that the deletion of wzx, but not wcaJ, impairs the virulence of P. salmonis in an intraperitoneally infected Atlantic salmon, Salmo salar, model of piscirickettsiosis. Our findings support a role for LPS in the virulence of P. salmonis during the onset of piscirickettsiosis.